“I TAKE CARE OF THE WORLD”: CONSTRUCTION OF THE SENSE AND AXIOLOGICAL ATTITUDE OF CLARICE LISPECTOR’S CHRONICLE (Muitas Vozes, 2021)
Clarice Lispector’s activity as a chronicler constitutes the starting point of the present study, which has as the main object of understanding the singularity of Lispector’s chronicle, under the framework of the interferences of the content, of the compositional construction and of the style on the sense’s construction. This bias, of Bakhtinian inspiration, pursues the comprehension of the problem of the creative consciousness in the exercise of its axiological attitude which is inseparable of the production of speeches. The approach, however, particularizes the evaluative dimension, committed with the hypothesis of an architectural form that connects itself to the testimony as antagonist of the news.